Moderating Role of Foreign Investor Characteristics on the relationship between Regulatory Factors of International Trade and Environmental Degradation in UAE - Albahar, Saood Mohammad Hassan; Islam, Rabiul (South Asian Journal of Social Sciences and Humanities, 2022)
The study has been conducted to analyze the moderating role of economic factors of foreign  investor over the relationship between regulatory factors and environmental degradation in Dubai.  The study has been conducted in Dubai considering the country as a fastest growing economy and  attracting foreign direct investment in all fields. For the purpose of fulfilment of the study  objectives the research developed two hypotheses. The hypothesis was tested over a sample of 335  responses generated from the executives of multinational firms of Dubai. The results confirmed  that regulatory factors have a direct impact over environmental degradation, similarly, foreign  investor characteristics also have a significant moderating role over the significant relationship  between regulatory factors of foreign direct investment and environmental degradation. The study  is important for the policy makers to develop such rules that negative influence over the  environment may be curtailed.
Keywords: foreign direct investment; foreign investor characteristics; environmental degradation; regulatory factors